Cholesterol: how to measure and how to treat. (2nd October 2022) - Pottle, Alison
Abstract : Raised lipid levels are a significant risk factor for cardiovascular disease. Alison Pottle provides an overview of how these are measured and the lifestyle measures and medications that can be used to reduce risk in these patients Cardiovascular disease (CVD) is the leading cause of death in England and Wales. Raised lipid levels are a significant risk factor for CVD. Lipids are a heterogeneous group of substances which include cholesterol, triglycerides, lipoproteins and apolipoproteins. The link between increased lipid levels and atherosclerosis was first established in the early 1900s. Numerous clinical studies have demonstrated the critical role of low density lipoproteins and other cholesterol-rich apolipoprotein-B containing lipoproteins in atherosclerotic plaque formation and the subsequent risk of CVD events. There is now clear indication that the lower the achieved LDL levels, the lower the risk of CVD. Multiple interventions including changes in lifestyle together with the use of lipid-lowering therapies may be required to achieve desired lipid levels, and practice nurses can play a key role in this. This article will discuss how cholesterol levels are measured and the treatment strategies now available.